Shifting Patterns of Settlement in the Highlands of Central Jordan during the Early Bronze Age - Harrison, Timothy Paul ca. 20./21. Jh. (Bulletin of ASOR, 1997)
Survey data are a valuable source of archaeological information for tracing shifting patterns of human settlement, and they permit interpretive reconstructions of the changing organizational structure of regionally defined communities. In the semiarid highlands of central Jordan, Early Bronze Age survey data from the Madaba Plain region reveal a shift from a pattern of isolated site clusters concentrated along wadi systems or around perennial springs during the Late Chalcolithic/EB I to a more dense pattern configured in the form of a settlement hierarchy during the EB II-III. Models calculating the sustaining areas and rank-size distribution of known EB II-III sites, however, indicate a settlement system with a low level of integration and centralization. Rather than a truly urban culture, what emerged was a rural landscape composed of communities that remained self sustaining and sociopolitically autonomous while participating in limited production intensification. The settlement density reached during the EB II-III was reversed in the EB IV, with sites again confined to the principal wadi systems and springs in the region.